2016
DOI: 10.1055/s-0036-1597545
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Percutaneous Tenotomy

Abstract: Of the many treatment options for tendinopathy, percutaneous tenotomy has been used throughout the body with success. With this procedure, a needle is repeatedly passed into the abnormal tendon with the goal of converting a chronic degenerative process to an acute inflammatory condition that will progress to tendon healing. Ultrasound guidance for this procedure is essential to ensure that the abnormal region of the tendon is accurately targeted. The treatment has few contraindications, and negligible complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Needle shafts ( Figure 7 B) or metal implants can cause the reverberation artifact. This finding is useful for the identification of the needle tip during guided injections [ 24 ]. If the target is deep into the reverberation-affected area, adjusting the angle of insonation to be more oblique to the reflective plane can circumvent this artifact.…”
Section: Attenuation Of Ultrasound Signalsmentioning
confidence: 99%
“…Needle shafts ( Figure 7 B) or metal implants can cause the reverberation artifact. This finding is useful for the identification of the needle tip during guided injections [ 24 ]. If the target is deep into the reverberation-affected area, adjusting the angle of insonation to be more oblique to the reflective plane can circumvent this artifact.…”
Section: Attenuation Of Ultrasound Signalsmentioning
confidence: 99%
“…US-guided tendon fenestration has shown promising results in various chronic tendinopathies including CLE, 17 18 patellar 19 and gluteal tendinopathies. 15 20 In a 2006 retrospective study, McShane et al reported 63.6% excellent, 16.4% good, 7.3% fair and 12.7% poor outcomes at a mean follow-up of 28 months, in 58 consecutive patients with CLE treated with US-guided tendon fenestration, combined with a corticosteroid injection. 21 Two years later, in a retrospective study, the same authors reported on the results of US-guided tendon fenestration in a subsequent group of 57 consecutive patients with 57.7% excellent, 34.6% good, 1.9% fair, 5.8% poor outcomes at a mean follow-up of 22 months and concluded that a concomitant corticosteroid was not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to disrupt areas of tendinosis and cause local bleeding to stimulate physiological mechanisms of fibroblastic proliferation and tendon healing through scar remodelling. 15 Hence, the rationale behind this treatment is to convert a chronic degenerative painful process into an acute inflammatory condition that can lead to tendon regeneration and healing. 16 Bleeding that occurs within the tendon during the procedure delivers growth factors and inflammatory cells that are essential to initiate the first phase of tendon healing response.…”
Section: Introductionmentioning
confidence: 99%
“…Any type of tenotomy can be considered a regenerative technique because ensuing microtrauma induces a healing response through an early gene expression (transcription factors) pattern similar to mechanical loading, thereby enhancing tendon structure and strength [8]. The goal is to convert a chronic degenerative process into acute inflammation by breaking the vicious loop of failed healing and remodelling provoked by accumulated tendon damage [9]. Nevertheless, few controlled studies have examined the efficacy of percutaneous needle tenotomy for elbow epicondylopathy [10].…”
Section: Introductionmentioning
confidence: 99%